2020
DOI: 10.20956/jiks.v5i2.8931
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Freshwater Goby Species From the Biak and Koyoan Rivers, Luwuk Banggai, Central Sulawesi

Abstract: Sulawesi is an island famous for its biodiversity, including many endemic species. In particular, Sulawesi has the highest number of gobies in the world, including species with potential as food and/or ornamental fishes. The exploration of freshwater ichthyofauna is important in the context of Indonesian and global biodiversity. This research aimed to identify gobies found in the Luwuk Banggai area of Central Sulawesi, as a contribution to the exploration of Indonesian ichthyofaunal biodiversity. Gobies were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The lack of distribution and biological data of B. belobranchus potentially threatens the existence of the species. B. belobranchus as Eleotridae fish is also recorded in Danao, Cebu, Philippines (Ken et al, 2011), Sukamade River, East Java (Rukmana et al, 2014), Efate Island, Vanuatu (Bouffandeau et al, 2019), and Biak River, Central Sulawesi (Gani et al, 2019). B. belobranchus is one of the freshwater indigenous goby populations inhabiting the whole stretch of Mandulog River in Iligan City.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The lack of distribution and biological data of B. belobranchus potentially threatens the existence of the species. B. belobranchus as Eleotridae fish is also recorded in Danao, Cebu, Philippines (Ken et al, 2011), Sukamade River, East Java (Rukmana et al, 2014), Efate Island, Vanuatu (Bouffandeau et al, 2019), and Biak River, Central Sulawesi (Gani et al, 2019). B. belobranchus is one of the freshwater indigenous goby populations inhabiting the whole stretch of Mandulog River in Iligan City.…”
Section: Discussionmentioning
confidence: 98%
“…Studies regarding the discovery of several new species of goby fish in Indonesia Keith et al, 2012;Keith et al, 2015) as well as in other areas Mennesson et al, 2016;Keith et al, 2019) indicate that goby fish distribution is not only broad but also holds potential as high species diversity. Gani et al (2019) mentions that exploration of the species diversity of freshwater fishes, in particular gobies, contributes to the knowledge on the species richness of Indonesian ichthyofauna. The study has the potential to discover and to improve awareness regarding the dispersal of new and known species.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of S. longifilis in Karama River (Figure 2) has a different color with S. longifilis described by Gani et al (2019) in Biak River. The body coloration is dominated by brown in S. longifilis in Karama River, which is reported to be similar to S. longifilis from Japan (Maeda and Saeki 2018), while S. longifilis in Biak River is dominated by blue.…”
Section: Discussionmentioning
confidence: 82%
“…Penja fish was found by Nur et al (2018) in Karema River, West Sulawesi, but the genus has not been identified. Gani et al (2019) found Sicyopterus lagocephalus and S. longifilis in Biak and Koyoan River, Central Sulawesi. S. longifilis and S. pugnans were also identified by Olii et al (2019) in Gorontalo Bay and Bone River, Gorontalo waters.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation